Multiple paths to inequality. How institutional contexts shape the educational opportunities of second-generation immigrants in Europe. Issue 2 (14th March 2016) - Borgna, Camilla
ABSTRACT: Most cross-country studies on educational systems aim at identifying the net effects of single institutional aspects on students' outcomes. In this paper, I argue that educational systems are best conceived as configurations of interconnected elements. The aim of this paper is to provide a systematic assessment of how selected features of the educational system and of the immigration context combine in countries where second-generation immigrants severely underperform their native peers, net of socio-economic differentials. Using PISA data from 2006 and 2009, I compare the relative mathematics achievement of students with and without an immigrant background in 17 Western-European educational systems. The empirical results, based on fuzzy-set Qualitative Comparative Analysis, point to the existence of functional equivalents and institutional complementarities. Equally severe disadvantages can be found in the rigidly tracking systems of German-speaking and Dutch-speaking countries, but also in the highly comprehensive Scandinavian systems, where a delayed entry in the educational system is coupled with a wide distance from the language of instruction. Moreover, even in the absence of tracking, second-generation immigrants critically lag behind their native peers if they are overrepresented in schools with a poor learning environment.